Africa (Kenya and Tanzinia) - The Nature Conservancy (Symphony in the Flint Hills, 2015)
An introduction to African grasslands and the importance to the people living there. Eastern and southern Africa’s grasslands and savannas have been shaped over millions of years by volcanoes, seasonal droughts and fires, millions of grazing animals, and human activities.
Keywords: Africa; Kenya; Tanzinia; grassland; prairie; drought; wildlife; nature; nomads; Maasai; history; savannas